Tracing the Water–Energy–Food Nexus: Description, Theory and Practice. Issue 8 (August 2015) - Leck, Hayley; Conway, Declan; Bradshaw, Michael; Rees, Judith
Abstract The 'nexus' between water, energy and food (WEF) has gained increasing attention globally in research, business and policy spheres. We review the premise of recent initiatives framed around the nexus, examine the challenge of achieving the type of disciplinary boundary crossing promoted by the nexus agenda and consider how to operationalise what has to date been a largely paper exercise. The WEF nexus has been promoted through international meetings and calls for new research agendas. It is clear from the literature that many aims of nexus approaches pre‐date the recent nexus agenda; these have encountered significant barriers to progress, including challenges to cross‐disciplinary collaboration, complexity, political economy (often perceived to be under‐represented in nexus research) and incompatibility of current institutional structures. Indeed, the ambitious aims of the nexus—the desire to capture multiple interdependencies across three major sectors, across disciplines and across scales—could become its downfall. However, greater recognition of interdependencies across state and non‐state actors, more sophisticated modelling systems to assess and quantify WEF linkages and the sheer scale of WEF resource use globally, could create enough momentum to overcome historical barriers and establish nexus approaches as part of a wider repertoire of responses to global environmental change.